ENGLISH TEACHERS’ PROBLEMS IN IMPLEMETING CURRICULUM 2013 IN SMPN 2 WIH PESAM - Abadi, Ayuliamita (JR-ELT (Journal of Research in English Language Teaching), 2022)
This research is about the teachers’ problems in implementing curriculum 2013. It was conducted at SMPN 2 Wih Pesam. The aims of the research were to find out what problems are faced by those English teachers in implementing curriculum 2013 in SMPN2 Wih Pesam and to find out what are the teachers’ opinions about the change of curriculum. The design of this research was qualitative descriptive method. The subject of the research was the English teachers in SMPN 2 Wih Pesam. There were two English teachers in the school. The data was collected by using questionnaire and interview. The result showed that there were 4 problems faced by English teachers in SMPN 2 Wih Pesam. They were (1) the basic competence in curriculum 2013 cannot be modified, (2) lack of facilities, (3) the assessment, and (4) students’ low motivation. The result also showed that the English teachers agree that curriculum 2013 should be change, develop, and revise in some aspects to be a perfect curriculum.